ANALISIS KLASTER KECAMATAN DI KABUPATEN SEMARANG BERDASARKAN POTENSI DESA MENGGUNAKAN METODE WARD DAN SINGLE LINKAGE - Annisa Nur Fathia; Rita Rahmawati; Tarno Tarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Physical and non-physical aspects are the ways to explain a diversity among regions, including a diversity among districts. Village potential providing data about the existence, availability and development potential of each administrative area. To know the district that has the same characteristics, do the grouping using cluster analysis. Cluster analysis is a grouping of objects or cases into groups smaller where each group contains objects that are similar to one another. Clustering process is done for 19 districts in Semarang Regency by ward’s method and single linkage. Four cluster are chosen for the process of potential developing more specific in each district. From the analysis using ward’s method, 1st cluster obtained with minimal educational facilities. 2nd cluster with minimal health facilities. 3rd cluster with the districts which caracteristics itself have a good condition. 4th cluster with minimal power line facilities. From the analysis using single linkage method, 1st cluster obtained with a good condition of power line facilities. 2nd cluster with a good condition of educational facilities. 3rd cluster with a minimal educational facilities. 4th cluster with minimal power line facilities. R-Squared value from single linkage method is higher than ward’s method, this shows the single linkage clustering method produces cluster features with each other more heterogeneous compared to the clustering method ward. Keywords: Cluster Analysis, Ward’s Method, Single Linkage, Distict, Village Potential.